Kebijakan Pengelolaan Perikanan Berbasis Kearifan Lokal di Aceh - Sulaiman Sulaiman (Universitas Syiah Kuala, 2010)
ABSTRACT: Fisheries condition of Aceh is currently being critical. The condition was one of them caused by the pattern of fisheries management. In fisheries management in Aceh is known pattern of local wisdom in the form of hukom adat laot communities living in 147 lhoks. This wisdom pattern sets five key areas, namely laot abstinence, Laot custom, environmental maintenance custom, laot feast custom, and drifting item custom. The pattern is also recognized in the laws and regulations in Indonesia. But in reality, the traditional wisdom is implemented through the concept of division of roles among the government, fishermen, indigenous institutions, and other fisheries stakeholders. The Fisheries Management Policy Based on Local Wisdom